2009
DOI: 10.1186/1475-2875-8-43
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIa (CD32) polymorphism and anti-malarial IgG subclass pattern among Fulani and sympatric ethnic groups living in eastern Sudan

Abstract: Background: A SNP at position 131, in the FcγRIIa gene, affects the binding of the different IgG subclasses and may influence the clinical variation seen in patients with falciparum malaria. This study confirms and extends previous findings, analysing the FcγRIIa (CD32) polymorphism in relation to the IgG subclass distribution seen among two sympatric tribes living in eastern Sudan, characterized by marked differences in susceptibility to Plasmodium falciparum malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
6
29
0
Order By: Relevance
“…Clinically important polymorphisms occur in FcγRIIa (R134/H134; HR/LR) and FcγRIII (V158/F158), which influence IgG binding and are known to be associated with susceptibility to Gram-negative infection (15), autoimmune diseases (10, 13, 45), and malaria (23). Furthermore, a structural understanding of the impact of the receptor polymorphisms on recognition of different IgG glycoforms or subclasses is of particular importance for the development of effective Ab-based therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically important polymorphisms occur in FcγRIIa (R134/H134; HR/LR) and FcγRIII (V158/F158), which influence IgG binding and are known to be associated with susceptibility to Gram-negative infection (15), autoimmune diseases (10, 13, 45), and malaria (23). Furthermore, a structural understanding of the impact of the receptor polymorphisms on recognition of different IgG glycoforms or subclasses is of particular importance for the development of effective Ab-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the FcγRIIa-LR is the only receptor that binds human IgG2 (21), which interestingly is a major IgG class in autoimmunity (11) and in resistance to Gram-negative bacterial infection (15) and severe swine flu infection (22). A higher frequency of FcγRIIa-LR homozygous genotype was found to be associated with Plasmodium falciparum malaria resistance and consistently higher levels of anti-malarial IgG2 and IgG3 serum Ab (23). …”
mentioning
confidence: 99%
“…FcγR I and III have a preference for IgG1 and IgG3 and low affinity for IgG2 [63]. However, FcγRIIa has a high affinity to bind IgG2 [64]. This has potential impact on the transfer of antibodies directed to different antigens, because polysaccharides are likely to elicit more IgG2 antibodies [65,66], whereas IgG1 and IgG3 subclasses are directed primarily to proteins [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HBB, IL4, IL10, HLA-G, FCGR2A, G6PD, CD36 and tumor necrosis factor (TNF) have been associated with IgG or IgG subclass levels. 13,[16][17][18][19][20][21] However, there is no published genome-wide scan for IgG or IgG subclasses directed against P. falciparum antigens.…”
Section: Introductionmentioning
confidence: 98%
“…7 Furthermore, many studies evidenced the association of high levels of cytophilic IgG subclasses and reduced parasitaemia or risk of clinical malaria; [8][9][10][11] these include IgG1, IgG3 and also IgG2 for individuals carrying the H131 allelic form of FCGR2A. 12,13 In contrast, some studies revealed a potential anti-protective role of IgG4, which was associated with susceptibility to malaria, and which may block the protective effect of cytophilic IgG. 12 There is a growing body of evidence for human genetic factors controlling the level of IgG responses against P. falciparum antigens.…”
Section: Introductionmentioning
confidence: 99%